Some Fixed-Point Results via Mix-Type Contractive Condition. (10th March 2021) - Acar, Özlem
Abstract : We consider a fixed-point problem for mappings involving a rational type and almost type contraction on complete metric spaces. To do this, we are using F -contraction and H, φ -contraction. We also present an example to illustrate our result.